Efektivitas Konseling Apoteker dalam Menurunkan Tingkat Ketidakpatuhan Terapi Diabetes Mellitus - Abidin, Armawati; Rahmat, Rezqiqah Aulia (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Patient adherence to therapy is a crucial factor in the successful management of Diabetes Mellitus (DM). However, non-adherence remains a major challenge, leading to increased complications and treatment costs. This study aimed to determine the effectiveness of pharmacist counseling in reducing non-adherence to therapy in patients with type 2 DM. The study design used a quasi-experimental method with a pre-test and post-test approach without a control group. The sample consisted of 50 DM patients undergoing oral therapy at Community Health Center X. Compliance was measured using the Morisky Medication Adherence Scale (MMAS-8) questionnaire. The results showed a significant increase in patient adherence after receiving pharmacist counseling (p < 0.05). The conclusion of this study is that pharmacist counseling is effective in reducing non-adherence to Diabetes Mellitus therapy and should be implemented routinely in clinical pharmacy services.